Tractatus logioco-philosophicus / transleted by D. F. Pears & B. F. McGuinness - "Wittgenstein, Ludwig" (London, 1999)
Perhaps the most important work if philosophy written in the twentieth century, the Tractatus Logico-Philosophicus first appeared in 1921 and was the only philosophical work that Ludwig, Wittgenstein(1889-1951) published during his lifetime.
Keywords: "Philosophy, Western"